1988
DOI: 10.1016/0735-1097(88)90348-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of assessing coronary bypass graft patency with ultrafast computed tomography: Results of a multicenter study

Abstract: Because a significant number of all patients seen by cardiologists have had coronary bypass surgery, a relatively noninvasive method of assessing coronary bypass graft patency would be very helpful. Ultrafast computed tomography, by virtue of its rapid data acquisition time and reasonable spatial resolution, may be useful in this regard. To determine the sensitivity, specificity and predictive accuracy of this imaging modality as compared with cardiac catheterization, a multicenter study was undertaken. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…In most studies, the accuracy to detect bypass occlusion approached 100%. [211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] Clinically, however, it might be reasonable in most cases to not only assess the patency of the bypass graft but also the presence of coronary stenoses in the course of the bypass graft or at the anastomotic site, as well as in the native coronary artery system (Class IIb, Level of Evidence: C). This is more difficult, owing to the smaller caliber of these vessels, the presence of artifacts caused by metal clips, and the often pronounced coronary calcification.…”
Section: Follow-up After Bypass Surgerymentioning
confidence: 99%
“…In most studies, the accuracy to detect bypass occlusion approached 100%. [211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] Clinically, however, it might be reasonable in most cases to not only assess the patency of the bypass graft but also the presence of coronary stenoses in the course of the bypass graft or at the anastomotic site, as well as in the native coronary artery system (Class IIb, Level of Evidence: C). This is more difficult, owing to the smaller caliber of these vessels, the presence of artifacts caused by metal clips, and the often pronounced coronary calcification.…”
Section: Follow-up After Bypass Surgerymentioning
confidence: 99%
“…However, in the early stage of these studies, EBCT was only used as a tool for time-density curves of bypass grafts rather than to produce two-or three-dimensional images of the lumen of a coronary artery bypass graft. 15,24,25) Achenbach, et al showed that the assessment of bypass graft patency using three-dimensional images (EBA) obtained with EBCT yielded an accuracy of 100% in 25 patients with 56 bypass grafts. 16) Ha, et al found the sensitivity and specificity of EBA in revealing LIMA patency were 80% and 82.4%, and the sensitivity and specificity of EBA in revealing SVG patency were 91.7% and 91.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study using planar tomographic imaging with EBCT attained fairly good diagnostic accuracy (the sensitivity, specificity, and accuracy of detecting graft patency were 93.4%, 88.9%, and 92.1%, respectively). 15) For the purpose of obtaining more detailed information to understand the anatomy and status of graft patency, [16][17][18] recent advances in EBA technology have offered the challenge of constructing a three-dimensional image of the cardiac surface with coronary vessels. In this technology, a series of image data should be sampled at a specified trigger-time point of the cardiac cycle for several heart beats.…”
Section: Arteriesmentioning
confidence: 99%
“…Posteriormente fueron varios los grupos de trabajo que investigaron la permeabilidad de los injertos aortocoronarios por TC [27][28][29][30] . En los primeros estudios se concluyó que debido a los artefactos por movimiento respiratorio y latido cardiaco, el estudio de TC únicamente podía dirigirse a valorar la permeabilidad de los injertos aortocoronarios ya que técnicamente existían grandes dificultades para determinar la existencia estenosis en los injertos permeables.…”
Section: Valoración Angiográfica De La Permeabilidad De Injertos Aortunclassified